Integrating haptic simulation in dentistry: faculty insights and future directions - Hashem, Danya; Farag, Abeer; Algarni, Amnah A.; Mubarak, Rania Zahran; Hassan, Nisreen Nabiel; Alqussier, Anfal; Saleh, Somaya Ali (Frontiers in Oral Health, 2025)
PurposeEvaluate the knowledge of faculty members about haptic virtual reality simulation (HVRS) in dentistry and assess faculty members' perception towards the use of HVRS in dental education.MethodsThis interventional study involved distributing a questionnaire to 29 faculty members from different dental specialties as a baseline before attending a hands-on workshop on HVRS followed by another questionnaire distributed after the workshop. Data was analyzed using IBM SPSS version 26, employing chi-squared tests for statistical significance.ResultsAround 69% of faculty members had heard of HVRS prior to the study, but 86% had no prior experience using it. There was an increase in the willingness to use HVRS in teaching and to be included as an adjunct to pre-clinical and clinical training after attending the workshop. Post-training assessments indicated a significant shift in perceptions, with faculty expressing high satisfaction regarding the ergonomic design, visual system, and usability of the Simodont® simulator. Participants agreed that HVRS could enhance students' manual skills and self-evaluation capabilities.ConclusionFaculty members at Taibah University expressed a positive perception of the use of HVRS in dental education and a willingness to adopt HVRS as a teaching aid. They intend to incorporate it into pre-clinical and clinical training. Although the study has a small sample size, it highlights the need for ongoing faculty training to facilitate the integration of HVRS technology in dental education, while also calling for further research to explore its long-term effects on learning outcomes.